Using Video Modeling and Video Prompting to Teach Core Academic Content to Students With Learning Disabilities. Issue 3 (2nd July 2016) - Kellems, Ryan O.; Edwards, Sean
Abstract : Practitioners are constantly searching for evidence-based practices that are effective in teaching academic skills to students with learning disabilities (LD). Video modeling (VM) and video prompting have become popular instructional interventions for many students across a wide range of different disability classifications, including those with LD. This article provides readers with the knowledge necessary to understand VM, and includes directions and resources needed to implement an academic VM intervention for a student with LD.